Reduction in the numbers of drugs administered to elderly in‐patients with polypharmacy by a multidisciplinary review of medication using electronic medical records. Issue 4 (2nd May 2016) - Hayashi, Yuichi; Godai, Ayumi; Yamada, Megumi; Yoshikura, Nobuaki; Harada, Naoko; Koumura, Akihiro; Kimura, Akio; Okayasu, Shinji; Matsuno, Yasuko; Kinosada, Yasutomi; Itoh, Yoshinori; Inuzuka, Takashi
Abstract : Aim: Polypharmacy is a major problem for elderly patients in developed countries. We investigated whether a multidisciplinary medication review using electronic medical records could reduce the number of drugs administered to elderly patients receiving polypharmacy. Methods: The present study included 432 elderly patients (188 women, 244 men; 267 patients aged 65–74 years and 165 patients aged ≥75 years) who were admitted to and discharged from the Department of Neurology and Geriatrics, Gifu University Hospital, between 2004 and 2011; those who died at the hospital were excluded. The names, categories, and numbers of orally administered drugs at admission and discharge were examined retrospectively using electronic medical records. The histories of continuous oral immunotherapy use at the hospital, falls during the 2 years before hospital admission and the presence of fall risk factors were also evaluated. P ‐values <0.05 were considered statistically significant. Results: On average 1.14 ± 3.07 fewer types of drugs were given to patients at discharge than at admission in patients receiving polypharmacy ( P  < 0.001). However, the number of drugs given to patients undergoing continuous oral immunotherapy increased by 1.67 ± 3.47 ( P  < 0.001). The number of drugs was reduced in 33.1% of fallers, and 36.3% of non‐fallers. In both fallers and non‐fallers, there was a reduction in drug categories associated with falls. Conclusions: Multidisciplinary medication review using electronic medical records could significantly reduce the numbers of drugs taken by elderly inpatients receiving polypharmacy, including drugs associated with falls, in both fallers and non‐fallersGeriatr Gerontol Int 2017; 17: 653–658 .